THE EFFECTIVENESS OF ADDING KINESIOTAPING TO MICROWAVE DIATHERMY AND MASSAGE INTERVENTION IN REDUCING DISABILITY IN PATIENTS WITH MYOGENIC LOW BACK PAIN - Made Widnyana; Made Niko Winaya; I Putu Yudi Pramana Putra; Anak Agung Gede Eka Septian Utama; I Dewa Gede Alit Kamayoga; Made Yoga Prabawa (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
Myogenic low back pain (myogenic LBP) is a back pain caused by muscles as a source of pain. Myogenic LBP can cause disability in patients. Kinesiotaping is one of the new methods used to reduce disability in myogenic LBP patients. The purpose of the study was to find out the effectiveness of adding kinesiotaping to microwave diathermy and massage interventions in lowering disability in myogenic LBP patients. The study used experimental methods with pre-test and post-test control group design. There are two randomly selected groups with block permutation techniques. The treatment group consisted of 16 samples receiving interventions in kinesiotaping, microwave diathermy and massage. The control group consisted of 16 samples received microwave diathermy and massage interventions. Disability is measured by MODI questionnaire (Modified Oswestry Disability Index). The research was conducted at a physiotherapy clinic in Denpasar. The results of the study after the Paired sample T-Test in each group with a value of p<0.05, this showed that there was a significant difference between pre-test results and post-tests in each group. The inter-group different test was conducted with the Independent sample T-Test, obtaining a p<0.05, indicating that there were significant differences between the treatment group and the control group. Microwave diathermy provides a deep heating effect so that it can increase metabolism, reduce pain, reduce spasms and increase muscle extensibility. Massage interventions are able to reduce pain through gate control theory mechanisms. Pressure on the surface of the skin also stimulates the release of endorphins that will inhibit pain impulses to the brain. Kinesiotaping has the benefits of reducing pain, joint fixation, smoothing lymph flow and muscle facilitation. With this mechanism, the addition of kinesiotaping further decreases disability in myogenic LBP patients.